El Cortijo del Ahorcado (Baeza, Jaén) y la arquitectura monumental orientalizante en la Península Ibérica - Rodríguez Muñoz, Raquel; Bermejo Tirado, Jesús (Madrider Mitteilungen, 2020)
Zusammenfassung folgt.